Thoracic Endovascular Aortic Repair in Patients with Prior Open Aortic Surgery - Shimizu, Hideyuki (The Editorial Committee of Annals of Vascular Diseases, 2013)
Objective: To review our experience of thoracic endovascular aortic repair (TEVAR) in patients with prior open aortic repair (OAR). Materials and Methods: Stent-grafts were deployed in the arch, descending thoracic and thoracoabdominal aortae of 39, 13 and 5 patients, respectively, and in a deteriorated extra-anatomical prosthesis in one. The access route was the femoral artery in 10 of 23 patients with, and in 30 of 35 patients without a prior abdominal prosthesis. Prior prostheses and elephant trunks comprised 57 of 116 landing zones and 23 proximal landing zones, respectively. Results: Three patients died before discharge. Type II endoleaks developed in six patients, and Types I and III developed in one patient each. Type I endoleaks were not found at landing zones comprising prosthetic grafts. The overall actuarial three-year survival rate including early mortality was 86.5%. Conclusion: The clinical outcomes of TEVAR were excellent, even in patients with prior OAR. Prosthetic grafts, including elephant trunks, provided good landing zones for TEVAR. Prostheses with larger-caliber designs are recommended for iliac artery reconstruction in future TEVAR.